Diagnostic approach for cancer cells in urine sediments by 5‐aminolevulinic acid‐based photodynamic detection in bladder cancer. Issue 5 (6th April 2014) - Miyake, Makito; Nakai, Yasushi; Anai, Satoshi; Tatsumi, Yoshihiro; Kuwada, Masaomi; Onishi, Sayuri; Chihara, Yoshitomo; Tanaka, Nobumichi; Hirao, Yoshihiko; Fujimoto, Kiyohide
<x xml:space="preserve">Abstract</x> Bladder urothelial carcinoma is diagnosed and followed up after transurethral resection using a combination of cystoscopy, urine cytology and urine biomarkers at regular intervals. However, cystoscopy can overlook flat lesions like carcinoma in situ, and the sensitivity of urinary tests is poor in low‐grade tumors. There is an emergent need for an objective and easy urinary diagnostic test for the management of bladder cancer. In this study, three different modalities for 5‐aminolevulinic acid (ALA)‐based photodynamic diagnostic tests were used. We developed a compact‐size, desktop‐type device quantifying red fluorescence in cell suspensions, named "Cellular Fluorescence Analysis Unit" (CFAU). Urine samples from 58 patients with bladder cancer were centrifuged, and urine sediments were then treated with ALA. ALA‐treated sediments were subjected to three fluorescence detection assays, including the CFAU assay. The overall sensitivities of conventional cytology, BTA, NMP22, fluorescence cytology, fluorescent spectrophotometric assay and CFAU assay were 48%, 33%, 40%, 86%, 86% and 87%, respectively. Three different ALA‐based assays showed high sensitivity and specificity. The ALA‐based assay detected low‐grade and low‐stage bladder urothelial cells at shigher rate (68–80% sensitivity) than conventional urine cytology, BTA and NMP22 (8–20% sensitivity). Our findings demonstrate that the ALA‐based fluorescence detection assay is promising tool for the management of bladder cancer. Development of a rapid and automated device for ALA‐based photodynamic assay is necessary to avoid the variability induced by troublesome steps and low stability of specimens.